Students Narrative Essay Construction Ability - arbain, arbain (LPPM Universitas Mercu Buana Yogyakarta, 2017)
The researcher conducted the research to the Third Grade Students of SMK Negeri 9 Samarinda, which concerns to the Narrative Essay Construction Ability Made by the Twelve Grade Students of Fowl class. It is based on the researcher’s experience when he was a teacher in SMK Negeri 9 Samarinda. During the researcher taught, he found that English achievement of fowl class is cukup, but they had problems in using grammar, especially present perfect tense.In this study the researcher took 17 students as sample who were unique majoring for SMK in Samarinda and it is the only one in Samarinda. It is unique because breeding is usually a major in the university but now Samarinda has a vocational high school for learning animal cyclus.This research revealed that the ability of narrative essay construction of the students of the fowl department is fair. It is shown by the mean score that they get, that is, 66.11. second, almost of the students of fowl department of SMK Negeri 9 Samarinda difficult to write a narrative essay in egnlish well. It is shown by the percentage of the participants who get C.